ANTI:SMOKING: PACESETTER FOR NATION SEEN IN ADVANCING FRIEDMAN BILL (Tufts Archival Research Center, 2007)
Article reporting on the state of the tobacco industry. Quotes industry spokesmen as agreeing that smoking is on the decline, but arguing that those who do smoke should not be treated like second class citizens. Mentions that a tobacco bill being proposed right now that has the support of the tobacco industry is criticized for being "loop-hole ridden" and is a way for the industry to preempt any further regulation.